First genetic quantification of sex- and stage-specific feeding in the ubiquitous copepod Acartia tonsa - Ismar, Stefanie M.H.; Kottmann, Johanna Sarah; Sommer, Ulrich (Marine Biology, 2018)
Marine copepods provide the major food-web link between primary producers and higher trophic levels, and their feeding ecology is of acute interest in light of global change impacts on food-web functioning. Recently, quantitative polymerase chain reaction (qPCR) protocols have been developed, which can complement classic diet quantification methods, such as stable isotope or fatty acid analyses tools. Here, we present first results of feeding experiments assessing sex- and stage-specific food intake by the ubiquitous calanoid copepod Acartia tonsa by 18S targeted qPCR and microscopic grazing assessment. In triplicated mixed-diet feeding treatments, three suitable A. tonsa diets, the cryptophyte Rhodomonas balthica, the haptophyte Isochrysis galbana, and the diatom Thalassiosira weissflogii, were offered in equal biomass proportions under constant conditions. Prey uptake substantially varied between different algal species, as did the extent of sex- and stage-specificity of prey uptake. Male adult copepods had higher R. balthica gut contents than females, and nauplii contained more of this prey source than copepodites or adult copepods in mixed treatments. A trend towards higher amounts of ingested T. weissflogii in adult females than in males and in nauplii than in other stages was detected. Genetic gut content quantifications indicated low feeding on I. galbana, and no consistent sex- or stage-specific differences of I. galbana content in A. tonsa. Our results highlight diet-specific feeding differences between Acartia life stages and sexes, which can have implications on food-web dynamics and specific nutrient transfer to higher trophic levels in copepod populations of varying age composition under changing environmental parameters, such as rising temperatures and increasing ocean acidification.